2005
DOI: 10.1007/s00586-005-0936-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting outcome after whiplash injury in subjects pursuing litigation

Abstract: Records of 277 patients presenting for medicolegal reporting following isolated whiplash injury were studied retrospectively. A range of pre-accident, accident and response variables were recorded. Multivariate analysis was used to determine the main factors that predict physical and psychological outcome after whiplash injury. The factors that showed significant association with poor outcome on both physical and psychological outcome scales were pre-injury back pain, high frequency of General Practitioner att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
1
23
0
5
Order By: Relevance
“…Others interpret NOS to indicate more deliberate attempts by WAD patients to obtain "secondary gain." [45][46][47][48] The concerns here may range from hypochondriasis to frank malingering behavior. On this interpretation, the importance of psychological maladaptation is downplayed.…”
Section: Discussionmentioning
confidence: 99%
“…Others interpret NOS to indicate more deliberate attempts by WAD patients to obtain "secondary gain." [45][46][47][48] The concerns here may range from hypochondriasis to frank malingering behavior. On this interpretation, the importance of psychological maladaptation is downplayed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Lankester et al [22] and Turner et al [23] used information from GP reports and found that both physical and psychological outcomes were associated with pre-injury musculoskeletal complaints [23] and with preinjury back pain, high frequency of GP attendance, anxiety and depression symptoms [22]. It was concluded that these factors may represent vulnerability for a more unfavourable outcome after a neck trauma in a low velocity motor vehicle accident.…”
Section: Discussionmentioning
confidence: 95%
“…We could not explore the reasons for reporting of poor health at HUNT 1, as the questions concerning the self-reported pre-injury health were broad and non-specific. Both pre-injury anxiety and depression [22,26] and preinjury musculoskeletal pain [23] have been associated with whiplash and the course of symptoms after a whiplash injury. It is reasonable to assume that these factors contributed to poor pre-injury health also in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are other patients who have a more complex relationship between their emotional state and their physical disability, evidenced within my clinical practice and in the literature on chronic whiplash. [4][5][6][7] For example, patients who have a history of posttraumatic stress disorder (PTSD) may have this condition reactivated by a motor vehicle crash. In this setting, these patients often do poorly unless psychological factors can be addressed in addition to their physical pain.…”
Section: The Dreaded Dsmentioning
confidence: 99%